Imagination in educational theory and practice : a many-sided vision - Nielsen, Thomas William, 1969-; Fitzgerald, Robert; Fettes, Mark, 1961- (Cambridge Scholars Publishers, 2010)
Inspired by papers developed for the 6th International Conference on Imagination and Education: Imaginative Practice, Imaginative Inquiry (Canberra, Australia, 2008), this book connects a cross-section of educators, researchers and administrators in a dialogue and exploration of imaginative and creative ways of teaching, learning and conducting educational inquiry. Imagination is a concept that spans traditional disciplinary and professional boundaries. The authors in this book acknowledge diverse theoretical and practical allegiances, but they concur that imagination will play an essential role in the building of new foundations for education in the 21st century. From our conception of human development through our ways of educating teachers to the teaching of mathematics, they argue for the centrality of imagination in the realization of human potential, and for its relevance to the most urgent problems confronting our world. Introduced by a wide-ranging literature review and extensively referenced, this volume makes an important contribution to a rapidly expanding field.